UiTM Green Centre explores beverage carton recycling initiative with Tetra Pak - UiTM, UGC (UiTM Green Centre, 2025)
On 27 May 2025, the UiTM Green Centre, UiTM Shah Alam also held a meeting with Tetra Pak to explore opportunities to enhance sustainability initiatives, specifically through the beverage carton recycling project on the UiTM Shah Alam campus.